2001
DOI: 10.1097/00000539-200111000-00043
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactoid Reactions After Cisatracurium Administration in Six Patients

Abstract: We report six cases of anaphylactoid reaction after the administration of the muscle relaxant cisatracurium. They include two first-time documented anaphylactoid reactions after a precurarising dose. These incidents challenge existing views of a substantially reduced anaphylactoid potential of cisatracurium relative to other muscle relaxants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…As in our cases, many patients with severe anaphylactic reactions were not exposed previously to any NMBA [4-7]. The anaphylaxis may arise due to cross-reactivity to the tertiary and quaternary ammonium ions that are often found in foods, drugs and cosmetics [11].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As in our cases, many patients with severe anaphylactic reactions were not exposed previously to any NMBA [4-7]. The anaphylaxis may arise due to cross-reactivity to the tertiary and quaternary ammonium ions that are often found in foods, drugs and cosmetics [11].…”
Section: Discussionmentioning
confidence: 95%
“…Early clinical reports suggested that cisatracurium has negligible histamine-releasing potential and is a less potent trigger of allergic reactions than other NMBAs [3]. However, since 1995, several cases of cisatracurium-induced anaphylactic reactions with severe symptoms of cardiovascular collapse and bronchospasm have been reported [4-7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Tracheal intubation without muscle relaxants is possible with varying doses of remifentanil in combination with propofol or thiopental, and optimal conditions for direct laryngoscopic intubation have been investigated. [4][5][6][7] The optimal dose of remifentanil when used with thiopental for lightwand intubation without muscle relaxants has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their intended target, the nicotinic receptor on skeletal muscle, muscle relaxants can initiate bronchoconstriction via histamine release1,2, interaction with airway muscarinic receptors37 or anaphylaxis810. We have previously demonstrated that muscle relaxants that antagonize pre-junctional parasympathetic M2 muscarinic autoreceptors can potentiate vagal nerve induced bronchoconstriction6, a common event accompanying irritation of the upper airway during intubation and suctioning.…”
Section: Introductionmentioning
confidence: 99%